Training of Classroom Action Research for Science Teachers on Padang Pariaman’s SMPN 1, SMPN 2 Sintuk Toboh Gadang and SMPN 1 V Koto Kampung Dalam - Rahmah Evita Putri; Tuti Lestari (Fakultas MIPA Universitas Negeri Padang, 2018)
To improve the quality of learning and reflect on learning outcomes are things that really improve science teacher profesionalism. That is the biggest motivation for Universitas Negeri Padang’s community service team to make a training session about science learning on Padang Pariaman’s. Understanding the classroom action reaserch, science teachers can solve the learning problems and write their own scientific work. The purpose of this training are teachers can make their own classroom action research and do their own research untill they can make theirown journals. The result shows that the training was good and reach the target that reaserchers make. 16th proposal finished are more than enough. Proposal are the result from traning, with a lot of revition before the proposal really finished.